Evaluation of the role of combining inter-arm systolic pressure difference and derivatives of pulse volume recording in detecting subclavian artery stenosis - An, Xuanqi; Dong, Hui; Deng, Yu; Chen, Yang; Zou, Yubao; Zhang, Weiguo; Jiang, Xiongjing (Frontiers in Cardiovascular Medicine, 2022)
Background: Subclavian artery stenosis (SAS) is a peripheral arterial disease of asymptomatic appearance and disastrous consequences. The traditional screening method remains unsatisfactory. Objective: The study aimed to assess the diagnostic performances of inter-arm systolic pressure difference (IASBPD), derivatives of pulse volume recording (PVR), and their combination in detecting subclavian artery stenosis. Methods: The present study was a retrospective analysis of clinical data from inpatients suspected of supra-arch artery stenosis in Fuwai hospital during one year, who underwent selective arterial angiographies. We obtained simultaneous blood pressure measurements on four limbs and pulse waves for calculating IASBPD and PVR derivatives prior to the angiographies. We utilized the receiver operating characteristic curve (ROC) to calculate the optimal cut-off value of IASBPD, upstroke time (UT), and upstroke time per cardiac cycle (UTCC) for detecting SAS. Moreover, we compared the sensitivity and specificity of IASBPD, UT, UTCC, and their combinations for diagnosing SAS (Clinical trial number: NCT03521739). Results: We consecutively enrolled 320 eligible patients. Based on SAS's definition of stenosis above 50%, the area under the curve of IASBPD, UT, and UTCC were 0.84, 0.76, and 0.80 (P<0.001). And their corresponding cut-off points were 9mmHg, 202 milliseconds, and 23.2%. The sensitivity and specificity of IASBPD≥ 9mmHg were 57.0% and 94.1%. UT ≥202 ms and UTCC ≥ 23.2% yielded similar sensitivity (72.6% vs. 72.6%, P>0.05), but UTCC had higher specificity (81.1% vs. 72.4%, P<0.05). The sensitivity of the combination of IASBPD and UT (85.2%) or UTCC (78.5%) was significantly higher than IASBPD alone (57%, P<0.05). The specificity of either combination decreased to 67.6% and 76.8% (P<0.05). Conclusions: This present study showed that the combinations of IASBPD and PVR-derived parameters promoted diagnostic sensitivity and preserved adequate specificity than those alone for detecting SAS.